ANALISIS KETERLAMBATAN BONGKAR MUAT PUPUK BAGS PADA KM. ISA VICTORY DI PELABUHAN TELUK BAYUR PADANG - Zulwan; Achmad Ali Mashartanto; Bayu Yudho Baskoro; Fauziah Roselia; Vega Fonsula Andromeda (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research discusses loading and unloading activities, which are important in logistics operations in the maritime sector, including the transportation of bagged fertilizers. This study aims to analyze the factors causing delays in the loading and unloading of bagged fertilizers and efforts to address these delays in the loading and unloading activities on the KM. Isa Victory ship. The type of research conducted in this study was descriptive qualitative research using field observation, interviews, documentation studies, and fishbone data analysis techniques. The results of the study show that delays in unloading fertilizer bags are influenced by several factors, including port weather conditions, crew lack of understanding of SOPs, damage to loading and unloading equipment, lack of compliance with cargo arrangement procedures, cargo overload, and damage to cargo that is only detected during unloading. These factors are interrelated and cause disruption to loading and unloading activities. Efforts made based on the results of fishbone data analysis to overcome these problems include direct weather monitoring and monitoring through the BMKG Maritime Meteorological Station (STAMAR), routine maintenance of loading and unloading equipment, familiarization of new crew members and safety meetings, closing hatch covers during rainy conditions, repackaging damaged cargo, and implementing cargo calculation and stowage procedures.